Economia criativa e desenvolvimento: um estudo sobre a concentração de empresas dos setores de economia criativa na Região Metropolitana do Rio de Janeiro - Molina, Renier Crohare (2021)
In the context of transformations resulting from capitalism, globalization and the revolution in technology and information, the rise of creative activities has been shown to be a viable way to think about new productive models for territorial development. Therefore, this work aims to analyze the contribution of socioeconomic characteristics of the Metropolitan Region of Rio de Janeiro to the geographic concentration of companies in the Creative Economy sectors in the municipalities that make up this territory. The work has a bibliographical research stage, approaching concepts on Creative Economy, territorial development and contextualization of the economic and social dynamics of the RMRJ. The research also quantifies and specializes the enterprises of the Creative Economy segments, according to the criteria established by UNCTAD (2010) and presents the analysis of in-depth interviews with creative entrepreneurs from the research area. Thus, this study contributes to the understanding of how the creative sectors are organized in this territory, and showed that from a universe of 120,704 companies, 84.5% of the companies in the creative segment are concentrated in the Metropolitan Region of Rio de Janeiro. The research also identified through interviews the perception of entrepreneurs in the segment about the advantages and disadvantages of being located in this territory. This research seeks to be a strategic instrument, with inputs and data capable of impacting the planning of public policies and enterprises.